DEVELOPING STUDENTSâ€™ SPEAKING ABILITY THROUGH SUGGESTOPEDIA METHOD AT SMA TOMAKAKA MAMUJU - Arniati, Fitri (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2016)
This research was intended to find out whether or not suggestopedia can develop speaking ability of the second year students of SMA Tomakaka Mamuju. This research used pre-experimental method. The population of this research was the second year students of SMA Tomakaka MamujuÂ  in academic year 2014/2015. The sample was 25 students and used porpusive sampling technique.The result of this research showed that suggestopedia method can develop speaking ability of the students. It can be proven by the data of pre-test and post-test mean score, t-test value and t-table where pre-test and post-test 4,5, t-test value 11,04 and t-table 2,045. Post-test was higher than pre-test and t-test value was higher than t-table.